Pelatihan Bahasa Inggris melalui Test of English as a Foreign Language (TOEFL) Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Lampung - Sri Suningsih; Lidya Ayuni Putri; Resha Moniyana Putri; Sari Indah Oktanti Sembiring (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: This community service activity aims to provide knowledge and insight to students regarding strategies for dealing with questions in the TOEFL so that they can prepare for the real TOEFL test. The mastery of English skills especially TOEFL needs to be carried out as the alternative solution for students in preparing for graduation and working. Method: The methods used in this activity are training, coaching, monitoring, and evaluation. Results: This activity has achieved the expected goal of increasing students' knowledge and insight regarding the fast and appropriate way that can be applied in answering TOEFL questions. Conclusions: Based on tutorial observations for approximately 3 months of participating in TOEFL training, it shows that students' understanding in mastering the TOEFL material increased quite significantly.